Analysis Of Complaint Speech Act In The Help Movie By Tate Taylor - Khalifah, Amalia; , Agus Wijayanto, Ph.D; , Dra. Malikatul Laila, M. Hum (2013)
This research aims to describe the speech act of complaint strategy which are used in The Help Movie. The type of this research is descriptive qualitative research while the writer uses documentation and observation method as the method of collecting data. The data of this research are expressive utterances which are found in The Help Movie. The result of the research shows the speech act of complaint strategy mostly uses is Direct Accusation strategy. The intention which is regularly used of the characters in the movie is to warn, the complainer warn the complainee. The complainee‟s responses frequently used are verbal response strategy and explicit denial responsibility complainee response